Landslides in the Upper Submarine Slopes of Volcanic Islands: The Central Azores. (28th September 2021) - Chang, Yu‐Chun; Mitchell, Neil C.; Quartau, Rui
Abstract: Small landslides in the upper submarine slopes of volcanic islands present potential hazards locally because of their high frequency. We examine evidence for landsliding in high‐resolution bathymetric data from Faial, Pico, São Jorge, and Terceira islands of the Azores. Because the rugged morphology of the upper slopes makes landslides difficult to interpret, we develop two classification schemes for the 1, 227 identified slope valleys. One scheme addresses how recognizable the valleys were as originating from landslides (whether scarps are prominent or indefinite), whereas the other scheme addresses valley types (whether apparently produced by single or multiple failures). Size distributions are used to assess the relative occurrence of large versus small landslides. Thirteen landslides are predicted to have generated tsunami heights at source of >1 m and one with height of >7 m. Some slopes have gradients far above 30°, the angle of repose of incohesive clastic sediment, so the seabed in those areas is strengthened perhaps by carbonate cementation, by seismic shaking or by the presence of coherent lava or lava talus. Using all types of slope valleys, Faial and Pico have smaller affected volumes per unit slope area than those of São Jorge and Terceira. These differences could be associated with varied seismic activity, with more frequent earthquakes beneath Faial and Pico preventing the build‐up of sediments on their slopes. Submarine landslide statistics are therefore potentially useful for assessing long‐term earthquake hazards of volcanic islands in seismically active environments such as the Azores. Plain Language Summary: Many valleys are found in the underwater slopes of volcanic islands, and some of them are likely caused by submarine landslides. If such landslides were to occur today, they could generate tsunamis threatening local coasts. This research assesses such landslides in the Azores based mainly on high‐resolution echo‐sounder data. It illustrates methods that are potentially repeatable at other volcanic islands with suitable data. More than 1, 200 submarine valleys have been mapped. Thirteen of them would likely have generated tsunamis above the landslides with heights between 1 and 7 m, and hence potentially hazardous. Valleys produced by landslides around Faial and Pico islands are generally smaller than those around São Jorge and Terceira islands. These differences could be associated with more frequent earthquakes beneath Faial and Pico, which prevent the build‐up of thick sediment on their submarine slopes needed for large landslides. Studies of landslide occurrences around volcanic islands could therefore be useful to assess threats of tsunamis and earthquakes where these are not well documented by other methods. Key Points: Submarine slope landslide area and volume follow log‐normal probability density functions Landslide area and volume are markedly different between the islands, potentially a result of different long‐term seismicity Some landslides potentially generate tsunamis >1 m at source, which are hazardous due to short travel distances and recurrence intervals